Efektivitas Model Project-Based Learning terhadap Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Pusparadi, Ravindah; Saputri, Aprilia Eki; Darmayanti, Mela (SAP (Susunan Artikel Pendidikan), 2024)
This article aims to test and determine the effectiveness of the PjBL (Project-Based Learning) model in enhancing the creative thinking ability of class V students in learning IPAS in Elementary Schools. This research uses quantitative methods with pre-experimental type One Group Pretest - Posttest Design designs. The sample selected for this study was a student of V class SDN Z City of Tasikmalaya of 30 students who were selected using a purposive sampling technique. The study uses a test-shaped instrument with an open description of 15 questions in the form of a pretest and a posttest. Further, the data analysis is carried out through statistical tests of validity, reliability, normality, paired sample t-test, and n-gain. Based on the data obtained, the test instruments used in this study are valid and have a very high level of reliability. Based on the results, the project-based learning model is effective in improving creative thinking ability in learning IPAS students in the fifth grade of Elementary School.